Microsurgical autotransplantation for electric burn of the head - A. V. Sachkov (Трансплантология (Москва), 2018)
Introduction: Electric burns of the head are rare, and presents technical problem for reconstruction. Electric trauma leads to the formation of necrosis of the skin and bones, that with their small thickness of the head and the imminent accession of infection has no prospects of selfhealing and threatens to damage the brain and other intracranial structures. In such cases, use the traditional method autodermoplasty is impossible – necrotic bone will not allow the growth of granulation tissue. Reconstruction should be performed as early as possible with usage of vascularized flap. The tactics of early microsurgical reconstruction is the best.Materials and methods. Patient with fourth-degree electric burn of the head and face treated with method of free microsurgical flap autotransplantation in our Burn Center in 2011. Fasciocutaneous flap on radial artery and veins were successfully transferred.Results and discussion. Operation is performed on day 7 after injury. The donor site healed by primary intention. This flap allowed to closetemporo-mandibular joint, parotid gland, temporal and parietal bones. The ear canal are formed In the graft.Conclusions. Microsurgical reconstruction is the method of first choice in case of electric burns of head and face with necrosis of the skull bones.